PEACEBUILDING CONFLICT RESOLUTION ON IDENTITY CONFLICT, FORGIVENESS, AND RECONCILIATION: AN APPROACH FROM SOCIAL PSYCHOLOGY TO RESOLVING VIOLENT IDENTITY CONFLICT AND GROUP CONFLICT - Phan, Bora (ShodhGyan-NU: Journal of Literature and Culture Studies, 2025)
This work explores the intricate dynamics of identity conflict through the prism of social psychology, emphasizing the significance of forgiveness and reconciliation as essential instruments for resolving violent group conflicts. Identity disputes, which are often brought on by deeply rooted cultural, ethnic, or religious divisions, can lead to protracted hostilities and violence. We propose that understanding the psychological underpinnings of these conflicts can enhance the peacebuilding process. Using well-established social psychology concepts, the study argues that forgiveness is a collective effort that can break cycles of retaliation and hostility rather than just an individual act. Additionally, reconciliation is portrayed as a complicated process that involves acknowledging past wrongs, empathy for the adversary, and a shared commitment to peaceful coexistence. We demonstrate how psychological interventions centered on identity awareness, emotional regulation, and group dynamics can promote transformative conversations between disputing parties using case studies and empirical data. We offer practitioners engaged in peacebuilding initiatives a comprehensive approach by creating spaces that encourage communication and psychological healing, ultimately helping to resolve identity conflicts in a sustainable manner. According to our research, incorporating social psychology techniques into peacebuilding programs can greatly increase the likelihood that conflicts will be resolved successfully, fostering harmony in a variety of societies.